Quantum optics : an introduction - Fox, Mark (Anthony Mark) (Oxford master series in physics ;, 2006)
This book aims to introduce a wide range of topics at a lower level suitable for advanced undergraduate and masters level students in physics. The text is divided into four main parts, covering modern topics in both pure and applied quantum optics: I Introduction and background material. II. Photons. III. Atom-photon interactions. IV. Quantum information processing. The emphasis of the subject development is on intuitive physical understanding rather than mathematical arguments, although many derivations are included where appropriate.